2015
DOI: 10.1007/s10689-015-9823-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk reducing salpingectomy and delayed oophorectomy in high risk women: views of cancer geneticists, genetic counsellors and gynaecological oncologists in the UK

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…From our qualitative study, we identified the following factors important in the decision for salpingo‐oophorectomy or salpingectomy with delayed oophorectomy: ovarian and breast cancer risks; onset of premature menopause; level of evidence for the efficacy and safety of either strategy; medical history; family history; number of operations . The additional literature search yielded two publications on BRCA1/2 mutation carriers and professionals surveyed about salpingectomy with delayed oophorectomy. Factors reported to influence the decision are consequences of premature menopause, HRT, surgical morbidity, potential ovarian damage and lack of data on level of benefit and cancer risks …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From our qualitative study, we identified the following factors important in the decision for salpingo‐oophorectomy or salpingectomy with delayed oophorectomy: ovarian and breast cancer risks; onset of premature menopause; level of evidence for the efficacy and safety of either strategy; medical history; family history; number of operations . The additional literature search yielded two publications on BRCA1/2 mutation carriers and professionals surveyed about salpingectomy with delayed oophorectomy. Factors reported to influence the decision are consequences of premature menopause, HRT, surgical morbidity, potential ovarian damage and lack of data on level of benefit and cancer risks …”
Section: Resultsmentioning
confidence: 99%
“…The additional literature search yielded two publications on BRCA1/2 mutation carriers and professionals surveyed about salpingectomy with delayed oophorectomy. Factors reported to influence the decision are consequences of premature menopause, HRT, surgical morbidity, potential ovarian damage and lack of data on level of benefit and cancer risks …”
Section: Resultsmentioning
confidence: 99%
“…56 We found approximately 80% support among UK clinicians for such a study. 57 A trial in the UK (PROTEC-TOR study) is about to commence later this year.…”
Section: Risk-reducing Salpingectomymentioning
confidence: 99%
“…Among patients, the main concerns stem from awareness of the seriousness of OC, uncertainty about the risk reduction provided by PSDO, a family history of OC, and personal history of BC . Among caregivers, including gynecologic oncologists and geneticists, the main deterrents are scarcity of data on the level of benefit (83%), increased morbidity from adding a second procedure (79%), loss of BC risk reduction (68%), the need for long‐term follow‐up (61%), and possible failure by some women to complete the interval oophorectomy (66%) .…”
Section: Alternatives To Rrbsomentioning
confidence: 99%